Carotenoids from Haloarchaea and Their Potential in Biotechnology - Rodrigo-Baños, Montserrat (Mar Drugs, 2015)
The production of pigments by halophilic archaea has been analysed during the last half a century. The main reasons that sustains this research are: (i) many haloarchaeal species possess high carotenoids production availability; (ii) downstream processes related to carotenoid isolation from haloarchaea is relatively quick, easy and cheap; (iii) carotenoids production by haloarchaea can be improved by genetic modification or even by modifying several cultivation aspects such as nutrition, growth pH, temperature, etc.; (iv) carotenoids are needed to support plant and animal life and human well-being; and (v) carotenoids are compounds highly demanded by pharmaceutical, cosmetic and food markets. Several studies about carotenoid production by haloarchaea have been reported so far, most of them focused on pigments isolation or carotenoids production under different culture conditions. However, the understanding of carotenoid metabolism, regulation, and roles of carotenoid derivatives in this group of extreme microorganisms remains mostly unrevealed. The uses of those haloarchaeal pigments have also been poorly explored. This work summarises what has been described so far about carotenoids production by haloarchaea and their potential uses in biotechnology and biomedicine. In particular, new scientific evidence of improved carotenoid production by one of the better known haloarchaeon (Haloferax mediterranei) is also discussed.